Body-force and mean-line models for the generation of axial compressor sub-idle characteristics - Righi, Mauro; Ferrer-Vidal, Espana-Heredia Luis; Pachidis, Vassilios (Cambridge University Press, 2020)
This paper describes the application of low-order models to the prediction of the steady performance of axial compressors at sub-idle conditions. An Euler body-force method employing sub-idle performance correlations is developed and presented alongside a mean-line approach employing the same set of correlations. The low-order tools are used to generate the characteristic lines of the compressor in the locked-rotor and zero-torque windmilling conditions. The results are compared against steady-state operating points from three-dimensional (3D) Reynolds-averaged Navier–Stokes (RANS) computational fluid dynamics (CFD) simulations. The accuracy of the low-order tools in reproducing the results from high-fidelity CFD is analysed, and the trade-off with the computational cost of each method is discussed. The low-order tools presented are shown to offer a fast alternative to traditional CFD which can be used to predict the performance in sub-idle conditions of a new compressor design during early development stages
Keywords: CFD; Mean-line code; Through-flow code; Sub-idle performance; Axial compressor